IMPLEMENTASI PEMBELAJARAN PKN DALAM PEMBENTUKAN KARAKTER GENERASI MUDA GOOD AND SMART CITIZENSHIP DI ERA RESOLUSI INDUSTRI 4.0 - Taufika, Ryan; Amin, Zulkifli (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2023)
In the current era of the industrial revolution 4.0, learning is needed that can have a significant impact in answering opportunities and challenges in producing the quality and quality of the young generation with character who will become the future of the nation. This study aims to determine the implementation of Civics learning in Higher Education in shaping the moral character of Good and Smart Citizenship students in preparing the future of the nation. This type of research is qualitative, with analytical descriptive methods used to describe, analyze, and describe a condition of the subject or object under study based on facts that occur in the field about how to implement PKn learning. The subjects in this study are Civics lecturers and PKn students. Civics learning is very important in the formation of a nation character that is tough, competitive and able to solve social problems in the life of the nation and state. Civics learning fosters citizens to become good and smart citizens. Civics aims to develop the character and character of citizens in accordance with noble values and Pancasila.